Cover Image. (1st November 2018) - Zhang, Jing; Poudel, Bishow; Kenworthy, Kevin; Unruh, Joseph Bryan; Rowland, Diane; Erickson, John E.; Kruse, Jason
Abstract : The cover image, by Jing Zhang et al., is based on the Drought Stress article Drought responses of above‐ground and below‐ground characteristics in warm‐season turfgrass .https://doi.org/10.1111/jac.12301 .